Case Report: Concurrent de novo pathogenic variants in the LMNA gene as a cause of sporadic partial lipodystrophy - Santos, José L.; Miranda, José Patricio; Lagos, Carlos F.; Cortés, Víctor A. (Frontiers in Genetics, 2024)
IntroductionInherited lipodystrophies are a group of rare diseases defined by severe reduction in adipose tissue mass and classified as generalized or partial. We report a non-familial (sporadic) case of partial lipodystrophy caused by a novel genetic mechanism involving closely linked de novo pathogenic variants in the LMNA gene.MethodsA female adult with partial lipodystrophy and her parents were evaluated for gene variants across the exome under different mendelian inheritance models (autosomal dominant, recessive, compound heterozygous, and X-linked) to find pathogenic variants. Body composition was assessed via dual-energy X-ray absorptiometry (DXA).ResultsThe patient showed absence of adipose tissue in the limbs; preservation of adiposity in the face, neck, and trunk; muscular hypertrophy, hypertriglyceridemia and insulin resistance. DXA revealed a fat mass of 15.4%, with android-to-gynoid ratio, trunk/limb, and trunk/leg ratios exceeding the published upper limits of 90% reference intervals. Two heterozygous missense de novo pathogenic variants in cis within the LMNA gene were found in the proband: p.Y481H and p.K486N (NP_733821.1). These variants have functional effects and were reported in inherited Emery-Dreifuss muscular dystrophy 2 (p.Y481H) and familial partial lipodystrophy type 2 (p.K486N). Molecular modeling analyses provided additional insights into the protein instability conferred by these variants in the lamin A/C Ig-like domain.ConclusionIn a case of sporadic partial lipodystrophy, we describe two concurrent de novo pathogenic variants within the same gene (LMNA) as a novel pathogenic mechanism. This finding expands the genetic and phenotypic spectrum of partial lipodystrophy and laminopathy syndromes.